The Problems of Current Vaccinology - I.V. Bogadelnikov; A.V. Bobrysheva; Ye.А. Kruger; A.V. Ilyin; G.I. Smirnov (Zaslavsky O.Yu., 2013)
The article describes the possible causes of the unpredictable reactions of child's organism on vaccination and development of severe postvaccinal complications: epidemiological (uncontrolled group of children born from HIV-positive mothers and removed from the register upon reaching 18 monthes, and reduction in the selective pressure of contagious infectious diseases on human); genetic (lack of control and screening over the process of gene polymorphism, and the accumulation of point mutations); ignoring the immunological phenomena (antigenic imprinting and antibody-dependent amplification of infection).